E0078 The effect of acute atorvastatin on cardioprotection of ischaemic postconditioning in diabetes mellitus. (17th November 2010) - Ying, Fan; Shunsen, Yang; Yang, Cao; Lei, Ma; Shangjun, Liu; Yonglin, Huang; Weimin, Li
Abstract : Objective: This study was to investigate if the low dose of acute atorvastatin treatment could affect the cardioprotection of ischaemic post-conditioning (Ipost) in type 2 diabetes mellitus (T2DM) during ischaemia and reperfusion. Methods: Male Wistar rats and diabetic rats were randomly assigned to four groups: (1) nonconditioning group, (2) Ipost group, (3) acute atorvastatin–treated group (2 mg/kg/day atorvastatin for 3 days), (4) acute atorvastatin–treated group with Ipost. T2DM were induced with streptozotocin (40 mg/kg, i.p.) after 4-week high-fat diet. All rat hearts were allowed to stabilise for 30 min followed by 30 min of ischaemia and 120 min of reperfusion by the Langendorff technique, and they were divided into regional ischaemia (induced by ligation the left main artery) and global ischaemia (induced by clamping perfusion circuit). Postconditioning was achieved by six cycles of 10 s ischaemia-reperfusion periods after ischaemia. During reperfusion, the functional parameter, the peak rate of pressure development (+dP/dtmax ), was recorded at 5, 30, 60, 90 and 120 min in global-ischaemia protocols, and its recovery was expressed as a percentage of initial preischaemic values. At the end of perfusion, infarct area and risk zone of stained hearts were measured, and standard Western blot analysis was performed. Results: Postconditioning markly reduced infart size (the ratio of infarct area and risk zone, %) and improved the values of +dP/dtmax (data not shown) in standard-diet group (22.35±4.50% vs 44.51±3.53%, p<0.05), but failed in T2DM group (58.06±5.37% vs 57.38±5.11%, p>0.05). Acute atorvastatin treatment couldn't decrease ischaemia-reperfusion injury in the healthy and DM rat hearts (41.65±4.41% vs 44.51±3.53%, and 55.85±4.79% vs 57.38±5.11%, p>0.05). However, this short-term statin therapy didn't affect infarct size–limiting and contractile dysfunction-recovering of Ipost in healthy rat hearts (24.11±4.08% vs 22.35±4.50%, p>0.05), it restored the protection of Ipost in DM ones (35.65±4.93% vs 58.06±5.37%, p<0.05). Western blot analysis revealed that the phosphorylation of Akt Ser 473 and eNOS Ser 1177 increasing was indicated in Ipost group, but not in Ipost T2DM group. Acute atorvastatin treatment slightly increased the phosphorylated expression of Akt and eNOS both in healthy and in T2DM rats. 3-day statin application didn't further increase the phosphorylated Akt and eNOS levels of Ipost in healthy rats, but achieve the largest increasing in T2DM rats. Conclusions: Acute application of atorvastatin show cardioprotective effect in neither healthy rats nor in T2DM ones, and did not interfere with the protection of postconditioning in normal-diet rats, but could restore the infarct size-limiting and contractile dysfunction-reducing of Ipost in the diabetic rats. This study demonstrated that the mechanism was involved in increasing phosphorylation of Akt and eNOS.